2015
DOI: 10.3897/mycokeys.10.5126
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of ribosomal ITS PCR products creates frequent, non-random chimeric sequences – a test involving heterozygotes between Gymnopus dichrous taxa I and II

Abstract: Gymnopus dichrous exists in the southern Appalachians (USA) as two distinct entities with essentially identical nuclear ribosomal ITS1 sequences but differing ITS2 and LSU sequences (for convenience, called G. dichrous I and II). F 1 ITS heterozygotes between the two are routinely collected from nature. Cloning of ITS PCR products from F 1 heterozygotes produced sequences of both parental haplotypes but also numerous chimeric sequences (21.9%). The location of template switching was non-random leading to recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
5
8
0
Order By: Relevance
“…In analogy, for sequence types found only in a single study, some sound skepticism is perhaps in place given the sequence quality-related issues involved in studies based on cloning as well as next-generation sequencing (Hyde et al 2013;Lindahl et al 2013;Hughes et al 2015). However, there are examples to the contrary for both of these situations: sequence types found only in one particular study have proved to be authentic, and "species" found in several different studies have proved to be chimeras (Brown et al 2015;Nilsson et al 2015).…”
Section: Sorting Of the List Of Taxa (Sequence Or Study Count)mentioning
confidence: 92%
“…In analogy, for sequence types found only in a single study, some sound skepticism is perhaps in place given the sequence quality-related issues involved in studies based on cloning as well as next-generation sequencing (Hyde et al 2013;Lindahl et al 2013;Hughes et al 2015). However, there are examples to the contrary for both of these situations: sequence types found only in one particular study have proved to be authentic, and "species" found in several different studies have proved to be chimeras (Brown et al 2015;Nilsson et al 2015).…”
Section: Sorting Of the List Of Taxa (Sequence Or Study Count)mentioning
confidence: 92%
“…These usually do not focus on taxonomy, but just on a very rough classification, and consequently, quality control is not necessarily focussed on the DNA sequences generated due to the large amount of data. In addition, PCR can produce chimeric sequences ( Hughes et al . 2015 ), especially when DNA derived from multiple species is used (e.g.…”
Section: Ten Reasonsmentioning
confidence: 99%
“…Therefore, it is very important to detect and filter out such sequences to avoid false diversity estimates (Wintzingerode et al 1997), increasing the number of OTUs and novel discovery of ''species'' from erroneous sequence data (Smith et al 2010;Hoshino 2012). However, it is difficult to detect chimeras as normally they have a short length, and occur near the end of a template (Hughes et al 2015). Most fungal sequence data from high-throughput sequencing available in GenBank were obtained from amplicon sequencing, with ITS as the barcoding locus (Schoch et al 2012).…”
Section: Formation Of Chimerasmentioning
confidence: 99%